Toward sustainable dairy waste utilization: enhanced VFA and biogas synthesis via upcycling algal biomass cultured on waste effluent. Issue 1 (12th May 2015) - Smith, Simon A; Hughes, Eric; Coats, Erik R; Brinkman, Cynthia K; McDonald, Armando G; Harper, Jeric R; Feris, Kevin; Newby, Deborah
Abstract: BACKGROUND: In 2012, 9.3 million head of dairy cows in the USA produced an estimated 20 million metric tons of manure solids, but little value was gained from this manure. There is a pressing need to enhance manure resource recovery efforts, as dairy manure has potentially significant environmental impacts. This study evaluated components of an integrated suite of biological processes designed to maximize resource recovery from dairy manure, in which algae grown on polyhydroxyalkanoate (PHA) production effluent (PHA‐algae) were fermented and anaerobically digested to determine process impacts. RESULTS: A 10% PHA‐algae supplement produced 11% more volatile fatty acids (VFA) during fermentation and 11% more methane during anaerobic digestion (AD) (vs. dairy manure); the PHA‐algae biogas also contained a higher percentage (62.7 vs. 59.1%) of methane than manure biogas. Algal augmentation exhibited no negative effect on fermenter or AD operation. Quantitative polymerase chain reaction (PCR) showed that the ADs contained substantial po pulations of both acetoclastic and hydrogenotrophic methanogens, which, given the heterogeneous substrate, enhanced process stability. There were significant differences between PHA‐algae batches, and large quantities of COD were released during algae freezing. CONCLUSION: PHA‐algae yielded more VFA during fermentation, and a more methane‐rich biogas following AD than dairy manure. A 10% PHA‐algae supplement caused no process disturbance in normal manure flora. © 2015 Society of Chemical Industry